2019
DOI: 10.1002/ece3.5367
|View full text |Cite
|
Sign up to set email alerts
|

Parental genetic similarity and offspring performance in blue tits in relation to brood size manipulation

Abstract: In birds, as in many other taxa, higher genetic similarity of mates has long been known to reduce offspring fitness. To date, the majority of avian studies have focused on examination whether the genetic similarity of social mates predicts hatching success. Yet, increased genetic similarity of mates may also reduce offspring fitness during later life stages, including the nestling period and beyond. Here, we investigated whether parental genetic similarity influences offspring performance using data from free‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
(58 reference statements)
1
12
0
Order By: Relevance
“…In line with other studies (Brinkhof et al 1999, Garvin et al 2006, Arct et al 2019), we found that nestling body mass and environmental factors were significantly associated with the skin swelling following the first and second PHA injections, respectively. The body mass effect on the skin swelling after the initial PHA injection could simply reflect the development of the immune function in nestlings, since their body mass at this stage of rapid growth is dependent on hatching order (Smiseth et al 2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with other studies (Brinkhof et al 1999, Garvin et al 2006, Arct et al 2019), we found that nestling body mass and environmental factors were significantly associated with the skin swelling following the first and second PHA injections, respectively. The body mass effect on the skin swelling after the initial PHA injection could simply reflect the development of the immune function in nestlings, since their body mass at this stage of rapid growth is dependent on hatching order (Smiseth et al 2003).…”
Section: Discussionsupporting
confidence: 92%
“…extra‐pair offspring or within‐pair offspring) was added as a fixed effect. Mean ambient temperature during the nestling period and body mass on the day of the respective PHA injections were also entered as fixed effects, according to the previously shown effect of temperature and body mass on the PHA response (Brinkhof et al 1999, Garvin et al 2006, Fossøy 2007, Arct et al 2019). Additionally, because female condition has been correlated with yolk hormones (Verboven et al 2003) which again can affect the PHA response in the nestlings (Andersson et al 2004), we entered female body mass and tarsus length as fixed effects in the model, as an approximation of maternal effects.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous results may indicate that in this study population, avoidance of mating with genetically similar individuals should be favoured (Arct et al . 2017, 2019). Specifically, we showed that the genetic similarity of social parents negatively affected offspring performance (Arct et al .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we showed that the genetic similarity of social parents negatively affected offspring performance (Arct et al . 2019) because genetic similarity of parents negatively affected offspring immune responses. Moreover, we found a positive relationship between individual heterozygosity and body mass of female nestlings 14 days after hatching (Arct et al .…”
Section: Discussionmentioning
confidence: 99%
“…The genetic similarity of social mates not only can predict hatching success but also may affect offspring fitness of later life stages, including during the nestling period and beyond. As the genetic similarity of pairs increases, the weight and growth rate of offspring [ 93 ], fledging success [ 34 ], and offspring immunocompetence [ 94 ] significantly decline. Therefore, double-breeding females prefer to choose genetically dissimilar males.…”
Section: Discussionmentioning
confidence: 99%